Clustering Penggunaan Fuel Pada PT Trasindo Murni Perkasa Menggunakan Algoritma K-Means - Dini Anitasari; Wawan Joko Pranoto (Pusat Riset dan Inovasi Nasional, 2024)
In coal mining, vehicles are used that have a large physical shape so that they can carry quite a lot of material so that it doesn't take a long time to mine. A lot of fuel is used during mining. Mining units have an identification mark in the form of a unit number as the vehicle's identity. attached to the vehicle and this unit number will later be recorded in fuel usage. Due to the large amount of fuel consumed by each unit, a lot of data is collected and needs to be processed. In this study, researchers used the clustering method with the k-means algorithm. -means Clustering begins by determining the number of clusters. This research uses two clusters. The results obtained from this grouping are, units in the day shift have a higher consumption amount, namely 217 liters per unit, while units in the shift have a total consumption of 147 liters. per unit with an ARI value of 0.5399218293207123 and an NMI value of 0.6565191143081124.